Penerapan knowledge Management Dengan Konsep Mind Map menggunakan Smartphone Androiduntuk Capturing Dan Sharing Knowledge - Syahriani - STMIK Nusa Mandiri Jakarta (Bianglala Informatika, 2015)
ABSTRACT - The purpose of this study is to increase the participation of employees in knowledge sharing activities and reduce the gap in knowledge. To support these case, this study presents KMS android based application that can be accessed online via their mobile phone. KMS application is using the concept of mind mapping, because the giver of knowledge is not necessary to formulate his knowledge in the form of articles or manuscripts but enough to describe the framework of knowledge that will be presented to the reader, so that readers can quickly understand the content of the knowledge presented. In addition, this study also uses descriptive quantitative method to calculate the average value of the completed questionnaires by the respondents and perspective method to determine the response of the employee or comments regarding this application        android-based KMS. The results of these questionnaires can be concluded that the prototype-based KMS android application is acceptable and can be used properly by the employees of PT. Global Vision with an average value of 3,72. This application has received positive responses that can be seen from the results of the form responses and comments from the employees of PT. Global Vision. Keywords: Knowledge Management, Mind Map Concept, KMS-Based Android Application